Four economical moments of the Republican history of Peru - Mendoza Vidal, Jorge Américo (2018)
In almost two hundred years of republican history, we have passed for four economical moments. The first moment corresponds to the period of the “guano boom”, from 1830 to 1876. The second moment corresponds to the period of the called Aristocratic Republic, from 1894 to 1929. The third moment corresponds to the “exportation boom” that we live after the end of the Second World War, from 1943 to 1976. The fourth moment corresponds to the lasts twenty five years of economic growth through the application of neoliberal policies. It can be recognized a trend in each of these moments. Based on the scattered data it has been developed a diagram that permits recognize both phases, of boom and fall. It has been collected up-to-date statistics on research and information from economic specialists to write the history of these four moments. The particularity of these moments is that previously to the development of each one, there was always a debate on protectionist and industrialization policies against liberal positions from different nuances. First, Protectionism against Free Trade; then industrialization is proposed, continuing with Liberalism: “laisser faire”; then Keynesianism versus Neoliberalism. We can asseverate that the republican economic history has been developed in four economical moments clearly defined. JEL: N16